Comparison of the Catalytic Activity for o2 Reduction of Fe and Co mn4 Adsorbed on Graphite Electrodes and on Carbon Nanotubes - Zagal-Moya, J; Zagal-Moya, J; Silva-Gonzalez, N; Silva-Gonzalez, N; Oyarzun-Medina, M; Oyarzun-Medina, M; Tasca-Gottardo, F; Tasca-Gottardo, F (Royal Society of Chemistry, 2017)
We have compared the electrocatalytic activity of several substituted and unsubstituted Co and Fe N4-macrocyclic complexes (MN4) for the electro-reduction of oxygen with the complexes directly adsorbed on the edge plane of pyrolytic graphite or adsorbed on carbon nanotubes (CNTs). In the presence of CNTs, one order of magnitude higher surface concentrations of MN4 catalysts per geometric area unit could be adsorbed leading to a lower overpotential for the oxygen electro-reduction and activities in the same order of magnitude as the commercially available Pt/C catalysts in basic pH. From Koutecky-Levich regression analysis, the total number of electrons transferred was approximately 2 for all the Co complexes and 4 for all the Fe ones, both in the presence and in the absence of the carbon nanotubes. Furthermore, the Tafel slopes did not vary due to the presence of the CNTs and presented values in the range of -0.06 V decade-1 for the CoN4 compounds and in the range of -0.04 V decade-1 for FeN4. When plotting the log of kinetic current densities (i.e. logjk) at a constant potential for each complex divided by the surface concentration Γ, and the number of electrons transferred n for the ORR for each catalyst, versus the difference between the redox potential of the metal active site of the Co(ii)/(i) or Fe(iii)/(ii) catalyst and the reversible potential of the reaction they promote, the catalytic activity increases when the formal potential of the complex becomes more positive and the data obtained with complexes adsorbed on graphite are in agreement with the data obtained when using CNTs indicating that the increase in jk when CNTs are present is only due to an increase in the number of active sites per geometric area of the electrode. © the Owner Societies 2017.